2011
DOI: 10.1073/pnas.1100129108
|View full text |Cite
|
Sign up to set email alerts
|

Hund’s rule in superatoms with transition metal impurities

Abstract: The quantum states in metal clusters bunch into supershells with associated orbitals having shapes resembling those in atoms, giving rise to the concept that selected clusters could mimic the characteristics of atoms and be classified as superatoms. Unlike atoms, the superatom orbitals span over multiple atoms and the filling of orbitals does not usually exhibit Hund's rule seen in atoms. Here, we demonstrate the possibility of enhancing exchange splitting in superatom shells via a composite cluster of a centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
105
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 38 publications
9
105
2
Order By: Relevance
“…It reaches about 4 μ B , thus either indicating the valence state of iron to be closer to Fe 2+ , as for the case of diluted iron impurities in MgO, 28 or the Fe atom to be bounded to Mg ions. 29 We should note that XMCD experiments in our samples 30 showed neither mm induced on the MgO due to the proximity of the ferromagnet, nor a multiplet structure indicative of iron oxidation. We surmise the answer to this dilemma depends on a complex interplay between the structural changes and the charge-transfer process at the interface.…”
Section: Experiments and Modelmentioning
confidence: 99%
“…It reaches about 4 μ B , thus either indicating the valence state of iron to be closer to Fe 2+ , as for the case of diluted iron impurities in MgO, 28 or the Fe atom to be bounded to Mg ions. 29 We should note that XMCD experiments in our samples 30 showed neither mm induced on the MgO due to the proximity of the ferromagnet, nor a multiplet structure indicative of iron oxidation. We surmise the answer to this dilemma depends on a complex interplay between the structural changes and the charge-transfer process at the interface.…”
Section: Experiments and Modelmentioning
confidence: 99%
“…To achieve magnetic superatoms, a singely magnetic TM atom were embedded into a small simple-metal cluster, because either the D-state (magnetic state) of superatoms almost exclusively comes from atomic d-state (that is, for the filling superatomic shells, atomic d electrons are thought as delocalized valence electrons) or its superatomic D-state (magnetic state) hybridize strongly with atomic d-states (that is, atomic d electrons are strongly localized and not fill superatomic shells) in previous reports. 6,9,10,12,13,[29][30][31][32][33][34][35] The exchange-splitting between the majority of superatomic D shells (atomic d shells) and their minority states can resulted in by both cases of above, so a superatom can have a corresponding spin magnetic moment. However, the spin magnetic moment of one superatom may be very vulnerable to its surrounding environments, which restricts the practical applications of superatoms.…”
Section: Magnetic Analysis and Roles Of Tm's (M's) D Valence Electmentioning
confidence: 99%
“…This was in fact demonstrated for the first time in, what has by now become a cult paper in the area of cluster science, by Knight et al [3]. Na n clusters at sizes 8,18,20,40,58 and 92 were found to be more stable than the neighboring sizes. Analogy of the simple metal clusters was taken a step further when it was experimentally shown that clusters with one electron less than shell filling have large electron affinities (EA), like halogen atoms [4][5][6][7], and those with one electron more than shell filling have small ionization potentials (IP), like alkali atoms [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 72%
“…Noting that S, P, D… orbitals can accommodate maximum of 2, 6, 10,… electrons, clusters with 2,8,18,20,34,40,58,… valence electrons will have filled electronic shells, and hence will be more stable than their neighbors. This was in fact demonstrated for the first time in, what has by now become a cult paper in the area of cluster science, by Knight et al [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation